2001
DOI: 10.1210/jcem.86.1.7109
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Expression in Sertoli Cells as a Function of Seminiferous Tubule Maturation in the Human Cryptorchid Testis1

Abstract: Androgen receptor (AR) immunohistochemistry was performed in an archival collection of adult human cryptorchid testes to determine whether AR cellular distribution and intensity of immunostaining were functions of the severity of cellular dysgenesis. The seminiferous tubule histology of cryptorchid testes collected from adults is marked by three specific patterns. 1) Seminiferous tubules are characterized as maintaining focal areas of germinal cell differentiation (albeit incomplete) that are interspersed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 27 publications
(29 reference statements)
0
1
0
1
Order By: Relevance
“…Controverselly, in the current study we observed that the Leydig cells presented a smaller size and signs of degeneration despite being present in large numbers. A reduction in Leydig cell function has been shown in CO testes in rats ( 75 ) and humans ( 76 ), probably due to depletion of the smooth endoplasmic reticulum as it was described in humans ( 74 ).…”
Section: Discussionmentioning
confidence: 74%
“…Controverselly, in the current study we observed that the Leydig cells presented a smaller size and signs of degeneration despite being present in large numbers. A reduction in Leydig cell function has been shown in CO testes in rats ( 75 ) and humans ( 76 ), probably due to depletion of the smooth endoplasmic reticulum as it was described in humans ( 74 ).…”
Section: Discussionmentioning
confidence: 74%
“…Неопущение яичек также может быть связано с ТМ и наличием кластеров недифференцированных канальцев [24]. Поскольку неопущение яичек обычно диагностируют сразу после рождения, это состояние по определению имеет фетальное происхождение, что свидетельствует о связи внутриутробной задержки развития с незрелостью семенников [25].…”
Section: крипторхизмunclassified